2018
DOI: 10.1038/s41598-018-23199-4
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of CREB in The Regulation of VSMC Proliferation: Mode of Activation Determines Pro- or Anti-Mitogenic Function

Abstract: Vascular smooth muscle cell (VSMC) proliferation has been implicated in the development of restenosis after angioplasty, vein graft intimal thickening and atherogenesis. We investigated the mechanisms underlying positive and negative regulation of VSMC proliferation by the transcription factor cyclic AMP response element binding protein (CREB). Incubation with the cAMP elevating stimuli, adenosine, prostacyclin mimetics or low levels of forksolin activated CREB without changing CREB phosphorylation on serine-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…The activation of AKT/mTOR and MAPK/Erk signaling cascades by apelin phosphorylates p70S6K leads to HUVEC proliferation . Serine 133 phosphorylation of the cAMP responsive element binding protein (CREB) is at the endpoint of various signaling pathways, like growth factor signaling, and regulates vascular smooth muscle cell proliferation . That EV/Exs activated AKT and Erk cascade in HUVEC and phosphorylated the same residues of p70S6K and CREB, strongly suggest the implication of these cascades in EV/Exs‐induced proliferation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of AKT/mTOR and MAPK/Erk signaling cascades by apelin phosphorylates p70S6K leads to HUVEC proliferation . Serine 133 phosphorylation of the cAMP responsive element binding protein (CREB) is at the endpoint of various signaling pathways, like growth factor signaling, and regulates vascular smooth muscle cell proliferation . That EV/Exs activated AKT and Erk cascade in HUVEC and phosphorylated the same residues of p70S6K and CREB, strongly suggest the implication of these cascades in EV/Exs‐induced proliferation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional coactivators Yes-associated protein (YAP) and transcriptional co-activator with PDZ-binding motif (TAZ) also play an important role in linking actin cytoskeleton dynamics to gene expression and changes in cell behaviour [203]. In the nucleus, YAP and TAZ interact with members of the TEA domain (TEAD) transcription factors and several other components of the transcriptional machinery, to regulate gene expression [204,205] and promote cell proliferation [206]. The functions of YAP and TAZ are negatively regulated by the Hippo pathway kinases MST and LATS [207,208].…”
Section: The Role Of Actin Cytoskeleton Remodellingmentioning
confidence: 99%
“…Several studies suggested that CREB contributes towards the anti-mitogenic effects of cAMP in VSMC (see Figure 3). For example, stimuli that elevate cAMP and inhibit VSMC proliferation are associated with increased CREB activity [47,91,205,227]. Inhibition of CREB using siRNA-mediated silencing or expression of dominant-negative CREB increases VSMC proliferation [228,229,230], whereas expression of constitutively active CREB mutants is inhibitory [47,228,230].…”
Section: The Role Of Crebmentioning
confidence: 99%
“…Previous studies have shown CRTC2-deficient mice have normal glucose levels during both feeding and fasting conditions without any effects on hepatic glucose production [33], suggesting the contribution of CRTC2 to glucose homeostasis is limited. Additionally, serum increases the proliferation of vascular smooth muscle cells by inducing phosphorylation of CREB without regulating CRTC2 [34]. Thus, our results suggest DSCR1-4 induces gluconeogenesis by increasing the phosphorylation of CREB independently of CRTC2 phosphorylation.…”
Section: Discussionmentioning
confidence: 52%